Community-driven social innovation and quadruple helix coordination in rural development : Case study on LEADER group Aktion Österbotten - Nordberg, Kenneth; Mariussen, Åge; Virkkala, Seija (Elsevier, 2020)
Social innovations (SIs) are new ideas that create collaboration or new social relationships and thus meet local needs. The purpose of the research is to understand the role of SIs and community-based quadruple-helix actors in rural development. The research question is how do community-based quadruple-helix actors contribute to the formation of SI networks in the context of rural development? The triple helix model represents innovations as emerging in cooperation between three helices (university, industry, and government). The quadruple helix (QH) adds civil society as a fourth helix. Using the QH model in rural development requires a broad definition of the helices. In addition to universities, all types of educational and research institutes are important. In addition, different types of public organisations are important, not just the government. We define the fourth helix as representing civil society as a community, not just individual citizens. Our main argument is that the QH model fosters understanding of the variety of formal and informal ways in which SI enables societal development in rural areas. We examine the relevant relationships with the help of the strands of literature on SI and QH, and also a case study on projects conducted under the LEADER programme (Aktion Österbotten) in Finland. The case study is based on a narrative approach inspired by the learning history method, with the identification of critical incidents, which help us to identify how the QH evolves throughout successful community-driven SIs. The narrative approach reveals the significance of informal communities in transforming QH relations. Many projects under the LEADER programme aim to strengthen the attraction of communities by promoting local identity, including broad participation in collective events, such as enjoying nature, cultural events, sports, and other social activities. Many of those activities have the potential to spill over into other types of SI, such as entrepreneurship oriented towards tourism and new solutions to social needs. The decisive factor for the success of the projects was the involvement of local communities. The local knowledge of the communities was nourished in the projects in interaction with other local and extra-local QH actors. Accordingly, the main contribution of the paper is combining the notions of SI and the QH, and presenting the fourth helix as a community enabling rural development. We call this rural development model the community-driven QH model.
Keywords: Social innovation; community; quadruple helix; neo-endogenous rural development; narrative; Finland; fi=Aluetiede|en=Regional Studies|